Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the sum of [tex]\(4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}\)[/tex] in simplest form, let's break it down step-by-step and simplify each term separately.
1. Simplify the first term [tex]\(4 \sqrt[3]{x^{10}}\)[/tex]:
[tex]\[ 4 \sqrt[3]{x^{10}} \][/tex]
The cube root of [tex]\(x^{10}\)[/tex] can be written as:
[tex]\[ \sqrt[3]{x^{10}} = (x^{10})^{1/3} = x^{10/3} \][/tex]
So, the first term becomes:
[tex]\[ 4 \sqrt[3]{x^{10}} = 4 \cdot x^{10/3} = 4 x^{10/3} \][/tex]
2. Simplify the second term [tex]\(5 x^3 \sqrt[3]{8 x}\)[/tex]:
[tex]\[ 5 x^3 \sqrt[3]{8 x} \][/tex]
The cube root of [tex]\(8 x\)[/tex] is:
[tex]\[ \sqrt[3]{8 x} \][/tex]
We know that [tex]\(8\)[/tex] can be written as [tex]\(2^3\)[/tex], so:
[tex]\[ \sqrt[3]{8 x} = \sqrt[3]{2^3 \cdot x} = 2 \cdot \sqrt[3]{x} = 2 x^{1/3} \][/tex]
Therefore, the second term becomes:
[tex]\[ 5 x^3 \cdot \sqrt[3]{8 x} = 5 x^3 \cdot 2 x^{1/3} = 10 x^{3 + 1/3} = 10 x^{10/3} \][/tex]
3. Combine the simplified terms:
Now, sum the two simplified terms:
[tex]\[ 4 x^{10/3} + 10 x^{10/3} \][/tex]
These are like terms and can be added together:
[tex]\[ = (4 + 10) x^{10/3} \][/tex]
[tex]\[ = 14 x^{10/3} \][/tex]
Thus, the simplest form of [tex]\(4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}\)[/tex] is:
[tex]\[ 14 x^{10/3} \][/tex]
1. Simplify the first term [tex]\(4 \sqrt[3]{x^{10}}\)[/tex]:
[tex]\[ 4 \sqrt[3]{x^{10}} \][/tex]
The cube root of [tex]\(x^{10}\)[/tex] can be written as:
[tex]\[ \sqrt[3]{x^{10}} = (x^{10})^{1/3} = x^{10/3} \][/tex]
So, the first term becomes:
[tex]\[ 4 \sqrt[3]{x^{10}} = 4 \cdot x^{10/3} = 4 x^{10/3} \][/tex]
2. Simplify the second term [tex]\(5 x^3 \sqrt[3]{8 x}\)[/tex]:
[tex]\[ 5 x^3 \sqrt[3]{8 x} \][/tex]
The cube root of [tex]\(8 x\)[/tex] is:
[tex]\[ \sqrt[3]{8 x} \][/tex]
We know that [tex]\(8\)[/tex] can be written as [tex]\(2^3\)[/tex], so:
[tex]\[ \sqrt[3]{8 x} = \sqrt[3]{2^3 \cdot x} = 2 \cdot \sqrt[3]{x} = 2 x^{1/3} \][/tex]
Therefore, the second term becomes:
[tex]\[ 5 x^3 \cdot \sqrt[3]{8 x} = 5 x^3 \cdot 2 x^{1/3} = 10 x^{3 + 1/3} = 10 x^{10/3} \][/tex]
3. Combine the simplified terms:
Now, sum the two simplified terms:
[tex]\[ 4 x^{10/3} + 10 x^{10/3} \][/tex]
These are like terms and can be added together:
[tex]\[ = (4 + 10) x^{10/3} \][/tex]
[tex]\[ = 14 x^{10/3} \][/tex]
Thus, the simplest form of [tex]\(4 \sqrt[3]{x^{10}} + 5 x^3 \sqrt[3]{8 x}\)[/tex] is:
[tex]\[ 14 x^{10/3} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.